Indonesian humanitarianism : foundations, characteristics and contributions - Marzuki, Keoni (2022)
In the past two decades, Indonesia has become more active in humanitarian affairs, despite a preoccupation with natural hazards and political hurdles at home. In so doing, the Indonesian government employs “humanitarianism as diplomacy” — humanitarian action to promote its national interests — instead of deploying its efforts under a narrow understanding of humanitarianism. This is demonstrated in the country's humanitarian foci, which form part of its leadership ambitions in resolving crises in ASEAN and in supporting Muslim communities globally. As such, the Indonesian government's contributions are more pronounced in cases which promote Indonesia's regional and global leadership, such as in the Rohingya crisis and the Palestine issue. Indonesia also actively participates in disaster mitigation efforts in disaster-prone countries, which expands its international presence beyond ASEAN and the Middle East. This article identifies the foundation of Indonesia's humanitarianism and its key drivers, humanitarian contributions, and captures the involvement of state and non-state actors in such engagements.